2005
DOI: 10.1093/jnen/64.5.398
|View full text |Cite
|
Sign up to set email alerts
|

The p15INK4b/p16INK4a/RB1 Pathway Is Frequently Deregulated in Human Pituitary Adenomas

Abstract: Pituitary adenomas are common benign intracranial neoplasms. However, their tumorigenesis is not yet clearly defined. Inactivation of genes involved in the negative cell-cycle regulatory p15(INK4b) - p16(INK4a) -cyclin D/CDK4-RB1-mediated pathway (RB1 pathway) is one of the most common and important mechanisms in the growth advantage of tumor cells. Recently, much attention has been focused on the importance of alternative mechanisms of gene inactivation, particularly promoter hypermethylation in the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 33 publications
2
53
2
6
Order By: Relevance
“…A detailed analysis suggested that CDKN2A methylation was confined to particular adenoma subtypes (Simpson et al 1999) and these findings were subsequently confirmed by several other groups concluding that hypermethylation of the CDKN2A is the most common epigenetic deregulation in these neoplasias (Morris et al 2005, Ogino et al 2005, Yoshino et al 2007 INK4a is able to inhibit cell proliferation in pituitary tumor cells in correlation with a shift in the phosphorylation status of pRB, suggesting the relevance of this CDK inhibitor in the activation of pRB and pituitary tumor suppression (Frost et al 1999).…”
Section: Ink4 Inhibitorsmentioning
confidence: 80%
See 1 more Smart Citation
“…A detailed analysis suggested that CDKN2A methylation was confined to particular adenoma subtypes (Simpson et al 1999) and these findings were subsequently confirmed by several other groups concluding that hypermethylation of the CDKN2A is the most common epigenetic deregulation in these neoplasias (Morris et al 2005, Ogino et al 2005, Yoshino et al 2007 INK4a is able to inhibit cell proliferation in pituitary tumor cells in correlation with a shift in the phosphorylation status of pRB, suggesting the relevance of this CDK inhibitor in the activation of pRB and pituitary tumor suppression (Frost et al 1999).…”
Section: Ink4 Inhibitorsmentioning
confidence: 80%
“…Several studies based on immunodetection in tumor sections found abnormal expression of pRB in different pituitary adenomas. In some cases, decreased expression correlates with hypermethylation of the pRB promoter (Simpson et al 2000, Ogino et al 2005 or deletion within the protein-pocket binding domain (Simpson et al 2000).…”
Section: Retinoblastoma Proteinmentioning
confidence: 99%
“…In the latter group of tumors, the most common mechanism of CDKN2A inactivation involves methylation, while mutations or deletions are rare (13-16,26-28). Inactivation of the p16INK4a gene by methylation of the CpG islands in the promoter region has been reported to play a role in pituitary tumorigenesis, with a consequent decrease or abolishment of the p16 protein (7,27). Certain studies have shown an absence of the expression of p16INK4a at the level of mRNA and protein in all tumors examined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pRb pathway can be blocked through the loss of p16INK4a, pRb expression or CDK4 amplification. Such changes in the pRb pathway are expected to promote cell proliferation (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…INK4A by methylation is frequent in pituitary, mainly NFPA (Woloschak et al 1997, Simpson et al 1999a, Morris et al 2005, Ogino et al 2005, Yoshino et al 2007). Downregulation of p27 kip1 protein expression, likely due to a JAB1-mediated increased proteolysis (Korbonits et al 2002), is frequent in pituitary carcinomas and ACTH-secreting adenomas (Bamberger et al 1999, Lidhar et al 1999.…”
Section: The Cell Cyclementioning
confidence: 99%